2012
DOI: 10.5430/ijfr.v4n1p120
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and Impacts of Internal Credit Rating

Abstract: This study enrich the research in the area of credit rating by adding supportive power to the explanation of using factors which have an influence on the CR. Such a power can increase the awareness of the current situation of CR as a subject in one of the developing countries that has unique political and economic characteristics. The results in summary confirm that firm characteristic variables have a significant impact on CR. Profitability is positively associated with CR for all models, while leverage and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Al‐khawaldeh (2013) evaluated the impact of the firm characteristic factors upon the credit rating of Jordanian firms. The study concluded profitability to be positively associated with credit rating, and leverage and loss propensity to be negatively related to credit ratings.…”
Section: Review Of Literature and Theoretical Framework Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Al‐khawaldeh (2013) evaluated the impact of the firm characteristic factors upon the credit rating of Jordanian firms. The study concluded profitability to be positively associated with credit rating, and leverage and loss propensity to be negatively related to credit ratings.…”
Section: Review Of Literature and Theoretical Framework Of The Studymentioning
confidence: 99%
“…Again, it is well established that higher growth improves firm value as it provides good prospects for future cash flows (Chadha & Sharma, 2016). Thus, growth is expected to have a positive relationship with credit ratings (Adams et al, 2003; Al‐khawaldeh, 2013).…”
Section: Review Of Literature and Theoretical Framework Of The Studymentioning
confidence: 99%
“…Sedangkan jika ditinjau dari sisi investor, investasi dalam bentuk obligasi merupakan alternatif yang aman dibandingkan dengan investasi saham. [11] , Sari dan Badjra (2016) [12] , Arisanti et al (2014) [3] , Mahfudhoh dan Cahyonowati (2014) [7] , Widiyastuti dan Khusniyah (2014) [17] , Prabowo dan Sutjipto ( 2012) [9] , Alkhawaldeh (2012) [2] , Pandutama (2012) [8] , Sejati (2010) [13] , Adams dan Burton (2000) [1] . Faktor [6] rasio likuiditas atau sering juga disebut dengan nama rasio modal kerja merupakan rasio yang digunakan untuk mengukur seberapa likuidnya suatu perusahaan dengan cara membandingkan komponen yang ada di neraca, yaitu total aktiva lancar dengan total passiva lancar (utang jangka pendek).…”
Section: Pendahuluanunclassified